The relationship between Intima-Media Thickness and Carotid Plaque Characteristics with Incidence and Severity of Premature Coronary Artery Disease - Mohammad Haji Aghajani; Masoomeh Raoufi; Roxana Sadeghi; Faezeh Arefinia; Mohammad Parsa Mahjoob (Novelty in Biomedicine, 2023)
Background: Carotid intima media thickness (CIMT) and carotid plaque can predict premature coronary heart disease (PCAD) in patients hospitalized due to coronary artery disease or undergoing therapeutic interventions. This study aimed to determine the relationship between intima media thickness and carotid plaque characteristics with the incidence and severity of premature coronary artery disease.